Identifying and reducing disparities in successful addiction treatment completion: testing the role of Medicaid payment acceptance - Erick G. Guerrero; Bryan R. Garner; Benjamin Cook; Yinfei Kong; William A. Vega; Lillian Gelberg (BMC, 2017)
Abstract Background Medicaid has become the largest payer of substance use disorder treatment and may enhance access to quality care and reduce disparities. We tested whether treatment programs' acceptance of Medicaid payments was associated with reduced disparities between Mexican Americans and non-Latino Whites. Methods We analyzed client and program data from 122 publicly funded treatment programs in 2010 and 112 programs in 2013. These data were merged with information regarding 15,412 adult clients from both periods, of whom we selected only Mexican Americans (n = 7130, 46.3%) and non-Latino Whites (n = 8282, 53.7%). We used multilevel logistic regression and variance decomposition to examine associations and underlying factors associated with Mexican American and White differences in treatment completion. Variables of interest included client demographics; drug use severity and mental health issues; and program license, accreditation, and acceptance of Medicaid payments. Results Mexican Americans had lower odds of treatment completion (OR = 0.677; 95% CI = 0.534, 0.859) compared to non-Latino Whites. This disparity was explained in part by primary drug used, greater drug use severity, history of mental health disorders, and program acceptance of Medicaid payments. The interaction between Mexican Americans and acceptance of Medicaid was statistically significant (OR = 1.284; 95% CI = 1.008, 1.637). Conclusions Findings highlighted key program and client drivers of this disparity and the promising role of program acceptance of Medicaid payment to eliminate disparities in treatment completion among Mexican Americans. Implications for health policy during the Trump Administration are discussed.